Anti‐Epidermal Growth Factor Receptor Therapy in Head and Neck Squamous Cell Carcinoma: Focus on Potential Molecular Mechanisms of Drug Resistance. (2nd July 2013) - Boeckx, Carolien; Baay, Marc; Wouters, An; Specenier, Pol; Vermorken, Jan B.; Peeters, Marc; Lardon, Filip
Abstract : Targeted therapy against the epidermal growth factor receptor (EGFR) is one of the most promising molecular therapeutics for head and neck squamous cell carcinoma (HNSCC). EGFR is overexpressed in a wide range of malignancies, including HNSCC, and initiates important signal transduction pathways in HNSCC carcinogenesis. However, primary and acquired resistance are serious problems and are responsible for low single‐agent response rate and tumor recurrence. Therefore, an improved understanding of the molecular mechanisms of resistance to EGFR inhibitors may provide valuable indications to identify biomarkers that can be used clinically to predict response to EGFR blockade and to establish new treatment options to overcome resistance. To date, no predictive biomarker for HNSCC is available in the clinic. Therapeutic resistance to anti‐EGFR therapy may arise from mechanisms that can compensate for reduced EGFR signaling and/or mechanisms that can modulate EGFR‐dependent signaling. In this review, we will summarize some of these molecular mechanisms and describe strategies to overcome that resistance. Abstract : Targeted therapy against epidermal growth factor receptor (EGFR) is one of the most promising therapeutics for head and neck squamous cell carcinoma, and EGFR is overexpressed in a wide range of malignancies. An improved understanding of the resistance to EGFR inhibitors may provide new treatment options. This review summarizes some mechanisms and decribes strategies to overcome this resistance. Abstract : 摘要 针对表皮生长因子受体（EGFR）的靶向治疗是头颈部鳞状细胞癌（HNSCC）最有前景的分子靶向治疗之一。很多恶性肿瘤（包括HNSCC）存在EGFR过表达，EGFR启动了HNSCC肿瘤发生中的关键信号转导通路。不过，原发性和获得性耐药是严重的问题，导致了单一药物治疗缓解率低和肿瘤复发。因此，增进对EGFR抑制剂耐药分子机制的理解，可能为发现可在临床上用于预测阻断EGFR反应的生物标志物，以及确定克服耐药的新型治疗选择提供有价值的线索。迄今为止，临床上还没有HNSCC的预测性生物标志物。抗EGFR治疗耐药可能来自于代偿EGFR信号转导减弱的机制和/或可调节EGFR依赖信号转导的机制。在本综述中，我们将概述其中的一些分子机制，并对可克服耐药的策略加以描述。